Does caffeine intake enhance physical and physiological performance in swimmers? a systematic review and meta-analysis - Huang, Dongxiang; Huang, Bo; Wang, Zhongzheng; Takagi, Hideki; Chen, Yang; Huang, Zhuonan; Wang, Xiaobing; Tong, Xiangyue (Frontiers in Physiology, 2025)
BackgroundAcute caffeine intake is widely used by athletes to enhance performance, and its ergogenic effects are well-established in several land-based sports. However, whether similar benefits apply to swimming remains unclear.ObjectiveThis systematic review and meta-analysis (SRMA) evaluates the effects of acute caffeine intake on swimmers’ physical and physiological performance.MethodsFollowing PRISMA guidelines, studies were retrieved from five databases: Cochrane Library, Web of Science, Embase, PubMed, and SPORTDiscus. Eligible trials assessed acute caffeine effects on physical (25 m time, 50 m time, swimming velocity, jump height, power) and physiological (blood lactate, blood pH) outcomes in swimmers. A random-effects model was used to compute standardized mean differences (SMD) and 95% confidence intervals (CI). Subgroup analyses were conducted based on the type of outcome measures used.ResultsA total of ten randomized crossover trials involving 121 participants were included. Acute caffeine intake showed no significant improvement in 25 m time (SMD = −0.14; 95% CI: -0.91, 0.63; p = 0.73), 50 m time (SMD = −0.06; 95% CI: -0.50, 0.37; p = 0.78), swimming velocity (SMD = 0.47; 95% CI: -1.97, 2.92; p = 0.70), jump height (SMD = 0.12; 95% CI: -0.72, 0.96; p = 0.78) and power (SMD = 0.05; 95% CI: -0.78, 0.89; p = 0.90). Additionally, no significant effects were observed for blood lactate (SMD = 0.81; 95% CI: -0.07, 1.70; p = 0.07), and blood pH (SMD = 0.01; 95% CI: -1.86, 1.88; p = 0.99).ConclusionThis SRMA found no significant evidence that acute caffeine supplementation improves swimming performance, either physical or physiological. Given the small number and sample sizes of included studies and the presence of heterogeneity, the findings should be regarded as preliminary. Larger, well-designed trials are needed to clarify caffeine’s true effects on swimmers’ performance and to inform practical recommendations.